A new adaptation of the Interview-Informed Synthesized Contingency Analyses (IISCA): The performance-based IISCA. Issue 2 (3rd July 2022) - Iovino, Luigi; Canniello, Floriana; Simeoli, Roberta; Gallucci, Maria; Benincasa, Rosaria; D'Elia, Davide; Hanley, Gregory P.; Cammilieri, Anthony P.
ABSTRACT: The functional analysis of problem behavior is an important type of assessment that has been shown to increase the likelihood of arriving at an efficacious treatment. Several studies described the efficient use of the Interviewed-Informed Synthesized Contingency Analysis (IISCA) to reveal the variables that influence problem behavior across a variety of topographies, participants, and settings. In this study, we describe a new adaptation of the IISCA, the Performance-Based IISCA, used to assess the severe problem behavior of five Italian children with autism admitted to a clinic in the south of Italy. In all applications, the Performance-Based IISCA elucidated the synthesized establishing operations that evoked problem behavior and the synthesized reinforcers that influenced its maintenance. This study extends the literature on functional analysis by introducing the Performance-Based IISCA, demonstrating its viability with Italian clients and demonstrating how its procedural refinements can lead to safe analyses.